Practical Decision Making using Super Decisions v3 An Introduction to the Analytic Hierarchy Process - Mu, Enrique (SpringerBriefs in Operations Research,, 2018)
This book offers a simple introduction to the theory and practice of the Analytic Hierarchy Process (AHP) without a pre-requisite for a sophisticated mathematical background. AHP is an intuitive and mathematically simple methodology in the field of multi-criteria decision making in Operational Research (OR). Using Super Decisions v3, the newly developed software by the Creative Decisions Foundations, this book provides a quick and intuitive understanding of AHP using spreadsheet examples and step-by-step software instructions. Super Decisions v3 marks a drastic departure from the previous version 2 in terms of interface and ratings model development. In addition to a concise guide, instructional videos are also available to demonstrate how to use the different features of Super Decisions v3. Most AHP books assume the reader has basic OR mathematical background; however, AHP was developed with the goal that decision makers can take advantage of this methodology without struggling with the mathematics behind it. For this reason, only basic arithmetic knowledge is required from the readers. In conclusion, this book delivers a quick and practical understanding of the AHP methodology that can be useful for corporate executives and decision-makers in all fields.